Extend Cost Benefit Analysis of Bauxite Mining and Processing in the Central Highlands of Vietnam - Ngoc, Trinh Phuong; Co, Hoang Xuan (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 2, 2020)
The study focuses on assessing the effectiveness of bauxite mining and processing in the Central Highlands through the example of Tan Rai (Lam Dong) and Nhan Co (Dak Nong) bauxite-alumina complexes by the method of extended cost benefit analysis. External costs have been localized to be taken into account, including opportunity costs, environmental costs, corporate social responsibility costs and contingency costs for environmental incidents. The results showed that if calculating the environmental costs, the Tan Rai complex does not bring effectiveness for society with a negative NPV value (VND -5,167,422 million), IRR (6.27%) is lower than the discount (10%); Nhan Co complex is effective with positive NPV (VND 145,862 million), IRR (10.1%) is higher than the discount (10%), but the operation of this complex is risky when analyzing the sensitivity of the indicators. A ton of alumina will require an average from VND 0.7 to 0.9 million of environmental costs. In a year, two bauxite-alumina complexes in the Central Highlands create stable jobs for thousands of workers, contributing from VND 1,200 to 1,400 billion of taxes and fees for the State, equivalent to between VND 1.0 and 1.2 million per ton of alumina. From the lessons learned from Tan Rai and Nhan Co complexes, the future bauxite mining and processing projects need to be implemented on schedule and operate at 100% of the designed capacity right from the first year to achieve optimal efficiency. In the future, it is necessary to develop and evaluate the effectiveness of closed, full and chain options to improve the operational efficiency of bauxite projects, aiming to thoroughly solve the environmental issues by improving technological processes, implementing land restoration after mining, applying cleaner production solutions.